Analisis Efektivitas Segmentasi Pasar Dalam Meningkatkan Penjualan di Toko Eiger Kota Gunungsitoli - Jenni Hulu; Emanuel Zebua; Eliagus Telaumbanua; Nov Elhan Gea (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze the effectiveness of market segmentation in increasing sales at the Eiger Shop, Gunungsitoli City. Market segmentation is an important strategy in modern marketing that allows companies to divide the market into groups of consumers with similar characteristics. By focusing on the right market segments, companies can optimize resource allocation and increase sales. This research uses a descriptive qualitative approach, with data collected through interviews with business owners and direct observations regarding market segmentation carried out at Eiger stores. The research results show that market segmentation has a very large and significant influence on increasing sales at the Eiger Shop, Gunungsitoli City. Psychographic segmentation and consumer behavior were found to be the most influential factors in increasing sales. These findings provide important implications for Eiger Store management in designing more effective and efficient marketing strategies to increase sales in the future.